A regulaç\~ao de "novos temas" em acordos preferenciais de comércio celebrados por uni\~ao europeia, estados unidos, China e Índia: Pontos relevantes para o Brasil - Michelle Ratton Sanchez Badin (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– This study analyses the creation and implementation of rules in preferential trade agreements concerning government procurement, competition, environment and labour issues - all qualified as new topics to the international negotiations agenda on trade. It aims at identifying the main trends in selected agreements signed by the United States, the European Union, China and India, in contrast to ongoing processes of negotiation at the World Trade Organization, as well as to the Brazilian foreign trade policy towards the enlargement of the trade and trade related regulation by international agreements.
Keywords: K33; 330; regional agreements; WTO; competition; environment; public procurement; labour issues